Simulation of the motion of three methane molecules inside a closed carbon nanotube - Tarasov, Egor A. (Materials proceedings)
In this paper, the authors present the results of modeling the movement of three methane molecules into a closed carbon nanotube. The main approach in this work is to model the interaction between methane molecules and the structure of a nanocapsule, which is a single-walled closed carbon nanotube. Descriptively, the interaction is represented using molecular dynamics approaches and the Lennard-Jones potential. Methane molecules in this model are material points corresponding to the centers of mass of the molecules. To solve the resulting equations of motion of molecules inside the nanotube, the classical Runge–Kutta method is used.